Upaya Mengembangkan Kreatifitas dan Inovasi dalam Wirausaha Untuk Menghadapi Persaingan Pasar - Musyafa', Aang Yusril (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2017)
The aim of this article is to analyze the efforts of creatifity and innovation development in entrepreneurship in order to facing the market competation. By using literature study method finally obtained conclusion that in order to survive in the midst of market competation creative and innovative efforts can done by intrepreneurs are: Find out the relationship between onjects, processes, materials, technology, and people (employees). Develop a functional perspective, use reason appropriately, and remove feelings of doubt when going to do something.Keywords: kreatifitas, inovasi, wirausaha, persaingan pasar